2013
DOI: 10.1002/pbc.24856
|View full text |Cite
|
Sign up to set email alerts
|

Increased burden on caregivers of having a child with haemophilia complicated by inhibitors

Abstract: Caregivers of children with inhibitors reported higher impact of the disease compared to caregivers of children with no inhibitors. No differences between mothers and fathers in the two groups for SF-36, Caregivers' Burden Scale, VAS and IOF, except for domain pain in SF-36 where mothers reported higher impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 16 publications
3
76
0
1
Order By: Relevance
“…The strong association between inhibitor development and increased perceived burden for parents of children with haemophilia is not unexpected, and this result is consistent with previous research (DeKoven, Karkare, Kelley, et al, ; DeKoven, Karkare, Lee, et al, ; DeKoven et al, ; Lindvall et al, ; Ljung et al, ). Given this, the HCP must recognise and provide sufficient support to parents of children with inhibitors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The strong association between inhibitor development and increased perceived burden for parents of children with haemophilia is not unexpected, and this result is consistent with previous research (DeKoven, Karkare, Kelley, et al, ; DeKoven, Karkare, Lee, et al, ; DeKoven et al, ; Lindvall et al, ; Ljung et al, ). Given this, the HCP must recognise and provide sufficient support to parents of children with inhibitors.…”
Section: Discussionsupporting
confidence: 91%
“…However, a few studies have revealed the impact on parental burden. A cross‐sectional, international study using a generic instrument showed that parents of children with inhibitors reported a higher impact of the illness than parents of children without inhibitors (Lindvall et al, ). Lindvall’s et al () results are in line with two studies using an online questionnaire to identify areas of burden among parents of children with haemophilia (DeKoven, Karkare, Kelley, et al, ; DeKoven, Karkare, Lee, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers of children with hemophilia report reduced health‐related quality of life compared with caregivers of healthy children . Women are often the primary caretakers, and mothers of boys with hemophilia (BWH) are usually more involved in daily childcare than fathers and are believed to have higher risk for psychosocial problems .…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of bleeding and the demands of treatment increase the disease burden on patients and their families, leading to reduced quality of life, financial stress, and strained relationships. 3,4 For these reasons, improved management of patients with hemophilia complicated by an inhibitor is an important, timely challenge for the health care community. This chapter reviews current tools for the care of patients with inhibitors, focusing on treatment and prevention of bleeding and inhibitor eradication.…”
Section: Introductionmentioning
confidence: 99%